Arbaʻīn: tarjamah-ʹi manzūm-i chihil ḥadīs - Jāmī, 1414-1492 (Anjuman-i Jāmī, Riyāsat-i Tanvīr-i Afkār, Vizārt-i Maṭbūʻāt, 1964)
Forty Hadith (Islamic traditions); verse translation in Persian of Arbaʹūn al-nawawīyah Arabic word by Nawawi, 1233-1277.